Effectiveness of Percutaneous Pedicle Screw Fixation for Traumatic Thoracolumbar Spine Fracture - Gurung, Sandeep; DC, Gopal Sagar (Journal of Nepalgunj Medical College, 2022)
Introduction: Surgical treatment of thoracolumbar fracture without neurological damage has resulted in better clinical and radiological outcome than conservative treatment. Traditional open approach is associated with extensive paravertebral muscle damage and postoperative morbidity so percutaneous pedicle screw fixation is highly valuable alternatives.Aims: to evaluate the efficacy and outcome of percutaneous pedicle screw fixation in the treatment of traumatic thoracolumbar fracture without neurological deficit.Methods: This study was conducted in Nepalgunj Medical College, Nepalgunj in a time span of one year; total of 40 patients were included and treated with percutaneous pedicle screw fixation and followed up for 6months. They were evaluated clinically and radiologically.Results: 40 patients with thoracolumbar fractures were managed with percutaneous pedicle screw fixation with a mean operative time of 77.30 min and intraoperative blood loss was 88.38ml. There was significant improvement in cobb’s angle (mean difference 13.92 degree), vertebral body height loss (mean difference 37.7%) and visual analogue scale (mean difference 3.55) postoperatively. These improvements remained statically significant at 6months follow up.Conclusion: Percutaneous pedicle screw fixation is safe, valid and effective treatment of thoracolumbar fracture without neurological deficit.